KNOWLEDGE AND PRACTICES OF MIDWIVES REGARDING ZIKA VIRUS IN KENDARI, SOUTHEAST SULAWESI, INDONESIA - Ramadhan Tosepu; Indri Eka Artamevia Khaerun Nisa Patawari; Hariati Lestari; Siti Rabbani Karimuna; La Ode Muhamad Sety; Fifi Nirmala (Public Health of Indonesia)
Background: In 2016 Zika virus infection became an international public health emergency concern.